Uninterruptable Power Supply based on Switching Regulator and Modified Sine Wave - Anna Nur Nazilah Chamim; Muhammad Heru Gustaman; Nia Maharani Raharja; Iswanto Iswanto (Institute of Advanced Engineering and Science, 2017)
The availability of the electricity in doing a job lead to a dependency on it. If there is a sudden failure on electricity, it will result in unfinished works. To overcome the undesired situation because of wasting time, it is advisable to have your power supply. The power supply can serve to replace electricity temporarily, or it could be as a replacement for power supply of PLN’s (State Electricity Company) electricity nets to meet the daily electricity needs. Backup power available can sufficiently replace the source of PLN’s electricity nets with the output of square wave to the ordinary electricity needs. The type of the intended power supply is inverter system as a backup system that supplies daily electricity. In this case, it aims to change the DC (direct current) to AC (alternating current) voltages.